2005
DOI: 10.1007/s00330-005-2799-5
|View full text |Cite
|
Sign up to set email alerts
|

Acquired uterine vascular malformations: radiological and clinical outcome after transcatheter embolotherapy

Abstract: The purpose of this retrospective study is to assess the radiological and clinical outcome of transcatheter embolization of acquired uterine vascular malformations in patients presenting with secondary postpartum or postabortion vaginal hemorrhage. In a cohort of 17 patients (mean age: 29.7 years; standard deviation: 4.23; range: 25-38 years) 18 embolization procedures were performed. Angiography demonstrated a uterine parenchymal hyperemia with normal drainage into the large pelvic veins ("low-flow uterine va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
75
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(80 citation statements)
references
References 27 publications
2
75
0
3
Order By: Relevance
“…9,12,13 In our study, the causes of myometrial hypervascularity on postabortion day 10 were pathologically proven RPOC in 61.5% of cases and hydatidiform moles in 15.4%. There was no case of a uterine AVM, and hypervascular uterine lesions completely disappeared in all cases at an average of 16.54 ± 11.06 days (range, 7-48 days) after the second D&C. In the previously reported studies 1,3,4,11,12,14,15 and case reports, 5-7,9,10,16 nearly all AVMs and vascular malformations of the uterus were diagnosed within a few days to several weeks after term delivery, molar pregnancy, or induced or spontaneous abortion. Three large studies 1,3,4 reported that 23.4% to 63% of patients having Doppler findings of a uterine vascular malformation also had sonographic evidence of RPOC, which was pathologically confirmed to be trophoblastic tissue or molar pregnancy in almost all of those who underwent curettage.…”
Section: 13mentioning
confidence: 94%
See 2 more Smart Citations
“…9,12,13 In our study, the causes of myometrial hypervascularity on postabortion day 10 were pathologically proven RPOC in 61.5% of cases and hydatidiform moles in 15.4%. There was no case of a uterine AVM, and hypervascular uterine lesions completely disappeared in all cases at an average of 16.54 ± 11.06 days (range, 7-48 days) after the second D&C. In the previously reported studies 1,3,4,11,12,14,15 and case reports, 5-7,9,10,16 nearly all AVMs and vascular malformations of the uterus were diagnosed within a few days to several weeks after term delivery, molar pregnancy, or induced or spontaneous abortion. Three large studies 1,3,4 reported that 23.4% to 63% of patients having Doppler findings of a uterine vascular malformation also had sonographic evidence of RPOC, which was pathologically confirmed to be trophoblastic tissue or molar pregnancy in almost all of those who underwent curettage.…”
Section: 13mentioning
confidence: 94%
“…1,3 In a study of 17 women with uterine vascular malformations treated with embolization of the uterine arteries, hysteroscopic resection of residual trophoblastic tissue was performed in 6 cases within 1 to 2 weeks after the embolization procedure. 14 In almost all patients with CDS characteristics of a uterine AVM in the literature who had expectant management without uterine artery embolization because of the absence of heavy vaginal bleeding or molar pregnancy, spontaneous resolution of the lesion occurred within short periods, with mean times for resolution being 69.5 days (range, 40-112 days) in a study by Wiebe and Switzer, 16 5.3 weeks (range, 1 week-6 months) in a study by Timmerman et al, 1 and 6 weeks (range, 2-8 weeks) in another study by Timmerman et al 15 However, the term "malformation" describes defects in the structure of an organ resulting from an intrinsically abnormal process of development; therefore, spontaneous resolution of a malformation in a short period is unlikely. 17 In 2 recent studies of uterine artery embolization performed in patients with color Doppler findings suggesting a uterine AVM and heavy vaginal bleeding, a true AVM was detected on angiography in only 3 of 8 cases in the study by Timmerman et al 1 and in 3 of 18 cases (17%) in a study by Maleux et al 14 Kido et al 9 reported a patient in whom CDS, magnetic resonance imaging, and magnetic resonance angiography all suggested a uterine AVM, but pathologic examination after hysterectomy revealed only RPOC.…”
Section: 13mentioning
confidence: 99%
See 1 more Smart Citation
“…Uterine trauma is one of the leading causes for development of uterine artery vascular lesions in the form of acquired Arteriovenous Malformation (AVM) or pseudo aneurysm. [1][2][3][4][5] So far nearly 100 cases of uterine AVM and very few cases of pseudo aneurysm have been reported. Trauma, resulting from prior dilation and curettage (D&C), therapeutic abortion, uterine surgery, or direct uterine trauma may lead to development of acquired uterine AVMs.…”
Section: Introductionmentioning
confidence: 99%
“…terine artery embolization (UAE) has shown to be a valuable, minimally invasive alternative for the treatment of women with symptomatic leiomyomas, uterine vascular malformations, and postpartum hemorrhage (1)(2)(3)(4)(5)(6)(7)(8)(9). The procedure is performed with angiographic and fluoroscopic guidance.…”
mentioning
confidence: 99%